Effects of water on fingernail electron paramagnetic resonance dosimetry. (30th September 2016) - Zhang, Tengda; Zhao, Zhixin; Zhang, Haiying; Zhai, Hezheng; Ruan, Shuzhou; Jiao, Ling; Zhang, Wenyi
Abstract: Electron paramagnetic resonance (EPR) is a promising biodosimetric method, and fingernails are sensitive biomaterials to ionizing radiation. Therefore, kinetic energy released per unit mass (kerma) can be estimated by measuring the level of free radicals within fingernails, using EPR. However, to date this dosimetry has been deficient and insufficiently accurate. In the sampling processes and measurements, water plays a significant role. This paper discusses many effects of water on fingernail EPR dosimetry, including disturbance to EPR measurements and two different effects on the production of free radicals. Water that is unable to contact free radicals can promote the production of free radicals due to indirect ionizing effects. Therefore, varying water content within fingernails can lead to varying growth rates in the free radical concentration after irradiation—these two variables have a linear relationship, with a slope of 1.8143. Thus, EPR dosimetry needs to be adjusted according to the water content of the fingernails of an individual. When the free radicals are exposed to water, the eliminating effect will appear. Therefore, soaking fingernail pieces in water before irradiation, as many researchers have previously done, can cause estimation errors. In addition, nails need to be dehydrated before making accurately quantitative EPR measurements.